Efficacy of Osimertinib in EGFR-Mutated Advanced Non-small-Cell Lung Cancer With Different T790M Status Following Resistance to Prior EGFR-TKIs: A Systematic Review and Meta-analysis - Yi, Xiao-Fang; Song, Jun; Gao, Ruo-Lin; Sun, Li; Wu, Zhi-Xuan; Zhang, Shu-Ling; Huang, Le-Tian; Ma, Jie-Tao; Han, Cheng-Bo (Frontiers in Oncology, 2022)
Purpose Epidermal growth factor receptor (EGFR) T790M-negative/unknown advanced non-small cell lung cancer (NSCLC) patients lack subsequent approved targeted therapies. This meta-analysis aimed to assess the efficacy of osimertinib in advanced NSCLC patients with different T790M status after resistance to prior first- or second-generation EGFR-tyrosine kinase inhibitors (EGFR-TKIs), and to predict the subgroups that may benefit beside T790M-positive disease. Methods PubMed, Embase, Web of Science, and Cochrane Library databases were searched for relevant trials. Meeting abstracts were also reviewed to identify appropriate studies. Studies evaluating the efficacy and/or survival outcomes of osimertinib in patients with different T790M status (positive, negative, or unknown) after resistance to prior first- or second-generation EGFR-TKIs were enrolled, and data were pooled to assess hazard ratios (HRs) or relative risk ratios (RRs) in terms of overall survival (OS), progression-free survival (PFS), and objective response rate (ORR). Results A total of 1,313 EGFR-mutated NSCLC patients from 10 retrospective and one prospective study treated with osimertinib after resistance to first- or second-generation EGFR-TKIs were included. In overall groups, T790M-positive patients showed an improved OS (HR = 0.574, P = 0.015), PFS (HR = 0.476, P = 0.017), and ORR (RR = 2.025, P = 0.000) compared with T790M-negative patients. In the brain metastases subgroup, no significant difference in OS was observed between T790M-positive and T790M-negative patients (HR = 0.75, P = 0.449) or between T790M-positive and T790M-unknown patients (HR = 0.90, P = 0.673). In the plasma genotyping subgroup, PFS was similar between T790M-positive and T790M-negative patients (HR = 1.033, P = 0.959). Conclusion Patients with progressive brain metastases on first- or second-generation EGFR-TKIs can benefit from subsequent osimertinib therapy regardless of T790M status. Patients with plasma T790M-negative status and lack of tissue genotyping should be allowed to receive osimertinib treatment.